2021
DOI: 10.2217/fon-2020-1152
|View full text |Cite
|
Sign up to set email alerts
|

FLABRA, Frontline Approach for BRCA Testing in an Ovarian Cancer Population: A Latin America Epidemiologic Study

Abstract: Aim: FLABRA (NCT02984423) evaluated prevalence of BRCA mutations, genetic counseling and management approaches in patients with ovarian cancer in Latin America. Patients & methods: Patients with ovarian cancer from six Latin American countries were enrolled. Tumor samples were tested for BRCA mutations. In cases with BRCA mutations ( BRCA mut), blood samples were analyzed to determine germline versus somatic mutations. Medical records were reviewed for counseling approach and treatment plan. Results: From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In general, in 13–23% of the diagnostic histological samples from HGSOC patients, a pathogenic BRCA1 or BRCA2 gene variant can be found [ 43 , 44 ]. In the AGO TR 1 study, 6.3% of the included ovarian cancer patients had somatic BRCA1/2 gene mutations [ 45 ], while the FLABRA study showed a higher than estimated rate of tumor BRCA mutations in ovarian cancer patients in a Latin American population of 28%, without specifying whether it was at the germline or somatic level [ 46 ].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In general, in 13–23% of the diagnostic histological samples from HGSOC patients, a pathogenic BRCA1 or BRCA2 gene variant can be found [ 43 , 44 ]. In the AGO TR 1 study, 6.3% of the included ovarian cancer patients had somatic BRCA1/2 gene mutations [ 45 ], while the FLABRA study showed a higher than estimated rate of tumor BRCA mutations in ovarian cancer patients in a Latin American population of 28%, without specifying whether it was at the germline or somatic level [ 46 ].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…The full listing of the identified documents relevant to Clinical Question 4 is provided in Data Supplement 1 (Table S1), and data from the 14 identified studies is presented in Data Supplement 1 (Table S2). 3,[64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] The guidance in the identified documents was diverse and frequently specific to the cancer type addressed by the document. One reviewer (H.M.) summarized the recommendations in the guidelines, which were considered by the full panel, who then directed the further systematic review of primary studies noted in the Methods.…”
Section: Development Of Recommendationsmentioning
confidence: 99%